(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Problem formulation and the objective of this study is to determine the impact of employee engagement (X1) and organizational culture (X2) on intention to leave (Y) at PT. Cahaya Bumi Nasional Di Denpasar. The subjects of this study included PT staff only. National Earth Light in Denpasar in 2022, which is 106 people. The sample used in this study consisted of 51 respondents identified by proportional random sampling technique. Data for this study were collected through observations, interviews and questionnaires. The data analysis techniques used in this study are validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t-test and F-test. Based on the results As a result of the study, we can see that:(1) Employee commitment has a negative and significant impact on intention to leave. (2) Organizational culture has a negative impact on intention to quit. (3) Employee engagement and organizational culture have a positive and significant impact on intention to quit. The level of influence of the independent variables on sales intentions is 72.5%. Looking at the search results, PT. In the future, Cahaya Bumi Nasional in Denpasar will provide vocational training for its employees. Thanks to professional training, employees will be able to work optimally to achieve the company’s goals, because they already have the skills acquired through the professional training program provided by the company.